2012
DOI: 10.1007/s00239-012-9507-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny, Classification and Evolution of Conopeptides

Abstract: Conopeptides are toxins expressed in the venom duct of cone snails (Conoidea, Conus). These are mostly well-structured peptides and mini-proteins with high potency and selectivity for a broad range of cellular targets. In view of these properties, they are widely used as pharmacological tools and many are candidates for innovative drugs. The conopeptides are primarily classified into superfamilies according to their peptide signal sequence, a classification that is thought to reflect the evolution of the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 75 publications
4
86
1
Order By: Relevance
“…Despite a weak correlation between gene superfamilies and pharmacological properties, some functional redundancy among members of a same superfamily exists (56). To date, 16 empirical gene superfamilies (designated as A, D, I1, I2, I3, J, L, M, O1, O2, O3, P, S, T, V, Y) have been annotated (57), plus 31 novel superfamilies have been discovered during the past two years (38,39,46,(57)(58)(59)(60).…”
Section: Significancementioning
confidence: 99%
“…Despite a weak correlation between gene superfamilies and pharmacological properties, some functional redundancy among members of a same superfamily exists (56). To date, 16 empirical gene superfamilies (designated as A, D, I1, I2, I3, J, L, M, O1, O2, O3, P, S, T, V, Y) have been annotated (57), plus 31 novel superfamilies have been discovered during the past two years (38,39,46,(57)(58)(59)(60).…”
Section: Significancementioning
confidence: 99%
“…Peptides with none or one disulfide bonds are disulfide-poor conopeptides and those having two or more disulfides are disulfide-rich conopeptides [6], also termed as conotoxins. It is suggested that a distinction of conopeptides on the basis of cysteine content and arrangement is not phylogenetically justified [7]. Conopeptides can be classified into following three categories on the basis of their signal sequence, cysteine pattern or framework and molecular target.…”
Section: Classification Of Conopeptidesmentioning
confidence: 99%
“…Whereas most of the toxinological studies on cone snails carried out during the last three decades have focused on species that belong to only a few lineages (Puillandre et al 2012), several lineages remain largely understudied or even not studied at all, as is the case for Profundiconus (Puillandre et al 2014). Radular morphology suggests a most likely vermivorous diet.…”
Section: Remarksmentioning
confidence: 99%